HUBUNGAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA PRODI D-III KEBIDANAN STIKES MARANATHA KUPANG - Brigita Dina Manek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. This article is intended to investigate the effect of learning motivation on student learning achievement. The research design used is correlation, this study population is fourth semester students. sampling technique where all members of the population are sampled. Data collection in this study through 1 questionnaire, this technique is used to examine the learning motivation variable according to the measurements made. The location of the study is at the STIKes Maranatha Kupang campus. The results of statistical tests using the non-parametric test Spearman Rank correlation test with a significance level of 0.05 obtained p = 0.000, so H1 is accepted. This condition means that there is a very significant relationship between the level of learning motivation and the level of student learning achievement. The significance of this relationship is due to the high motivation of students in the D-III midwifery program at Maranatha Health College. This motivation arises because most of the needs of each student, according to Maslow's hierarchy of basic needs, are almost met, as evidenced by the answers to the questions in the questionnaire. Therefore, with this motivation, they are motivated to carry out activities or lectures that are their responsibility.